2016
DOI: 10.1002/slct.201600603
|View full text |Cite
|
Sign up to set email alerts
|

Probe the Binding Mode of Aristololactam‐β‐D‐glucoside to Phenylalanine Transfer RNA in Silico

Abstract: Understanding the interactions of drug molecules with biomacromolecules at a micro-scale level is essential to design potent drugs for the treatments of human genome diseases. To unravel the mechanism of binding of aristololactam-b-D-glucoside (ADG) and phenylalanine transfer RNA (tRNA Phe ), an integrated computational strategy combining quantum mechanics (QM) calculation, molecular docking and atomistic molecular dynamics (MD) simulation was present in this work. QM calculations were performed to derive the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In contrast, an electrostatic repulsion occurs between daunomycinone and nucleotide U 50 , resulting in the positive intermolecular ELE + EGB energies. As evidenced by our previous binding studies of peptides and RNAs 54,55 and of drug molecules and proteins, 56,57 the intermolecular VDW energy is responsible for binding specificity of biomolecules and the intermolecular ELE+EGB energy is for the binding affinity of biomolecules. Thus, we learn from Fig.…”
Section: Resultsmentioning
confidence: 89%
“…In contrast, an electrostatic repulsion occurs between daunomycinone and nucleotide U 50 , resulting in the positive intermolecular ELE + EGB energies. As evidenced by our previous binding studies of peptides and RNAs 54,55 and of drug molecules and proteins, 56,57 the intermolecular VDW energy is responsible for binding specificity of biomolecules and the intermolecular ELE+EGB energy is for the binding affinity of biomolecules. Thus, we learn from Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Three independent simulations were carried out for each peptide- boxB RNA complex in 120 ns to ensure that our systems reached an equilibrated state. To accurately evaluate the charge–charge interactions between charged (or polar) molecules, we employed a variable internal dielectric constant model to capture electrostatic shielding effects. Using the implicit-solvent MM/GBSA approach with the variable internal dielectric constant model, we postanalyzed the last 5 ns simulation trajectories of the peptide- boxB RNA complexes to calculate their binding free energies. Details of the procedures and postanalysis of the atomistic MD simulations can be found in our previous work …”
Section: Methodsmentioning
confidence: 99%
“…This was later improved by taking into account both the binding energy of the peptide-target complex and the free energy of the peptide when stabilized in the bound conformation . The peptide’s binding free energy and free energy in the bound state were calculated by using the implicit-solvent MM/GBSA approach with the variable internal dielectric constant model. An early version of the algorithm was used to computationally design a 15-mer peptide to have good ability to recognize human lysine tRNA species (tRNA Lys3 ), a primer for HIV reverse transcription. Synthesis of the computationally designed peptide and experimental characterization by the Agris group revealed that the designed peptide has an affinity ( K d = 0.05 μM) that is 10-fold better than that of a peptide identified experimentally via phage display …”
Section: Introductionmentioning
confidence: 99%